Field Guide to Gamification: Game Components and Motivation in Higher Education - Lenz, Laura; Stehling, Valerie; Haberstroh, Max; Isenhardt, Ingrid (Proceedings of the International Conference on e-Learning (Online), 2018)
Although digital and analogue games differ in many ways, they still trigger multiple types of gaming experiences, which, inter alia, entail sensation, fantasy, narrative, challenge, fellowship, discovery, expression and submission. Most games contain several of these gameplay categories, which predict the individual enjoyment of the game and therefore which type of player is attracted and motivated by which type of gaming experience. The match between game design and player perception can be modelled and measured using the Mechanics-Dynamics-Aesthetics (MDA) framework (Hunicke et al., 2004). In higher education, game elements are used to increase motivation or to trigger a change of behavior. This is called gamification, or in other words, the addition of game elements to existing processes. However, there is a research gap concerning the measurement of motivation created by gamification and which type of player is attracted by which kind of gameplay. At RWTH Aachen University in Germany, the Cybernetics Lab IMA/ZLW & IfU is working on the implementation of a student-centric gamification design into a mandatory mechanical engineering lecture called Communication and Organizational Development (KOE I). Up to 1,500 freshmen apply every year. As has been shown in a recent study, there is an increased student demand for gamification, especially in the study entrance phase (Lenz et al., 2017). Students expect that gamification will make learning more enjoyable and motivate them. This PhD research paper deals with the question of what lecturers need to take into consideration in order to apply game elements in their courses to increase student motivation. The hypothesis is that the key component to increased motivation is a match between individual motivational types and MDA taxonomies as well as a deliberate transfer into gamification scenarios. How can lecturers actively predict which gaming experience students desire and how can they produce playful activities that satisfy these needs? The results of this thesis shall serve as a first step to a gamification field guide in higher education beyond interdisciplinary borders.